If I still want to breathe - Billie, Ayanda (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
One theme of this collection is the joy and the deep seated grief of my community of Kwa-Nobuhle; the brightness of hope on the faces on children running around our streets, the strides made by their mothers, the confusion of factory workers who are lost in darkness since the dawn of new dispensation. Then there are more personal poems: my own joys as well as the difficulties that have kept me from sleep and strangled my dreams as a writer, even though like Mafika Gwala, I believe that "words are born the way mothers beget children/words are born to survive time" . My style is influenced by imagistic, mystic and soulful poetry, such as the haunting Spanish voice of Garcia Lorca who wrote "I lose myself in the heart of certain children" and the absorbing isiXhosa voice of S E K Mqhayi. In response to their poetry my offering will be words that enliven us; my style will be what I see in the mirror, through the window, the sound of rain on my zinc roof and what frightens me.,Ndixomoloze ndiboph' amaxonya, ndisenza eli linge lokuzama ukuxhathalaza kulo msinga uzakutshayela ulwimi lwethu. Nantso ke incwadana ndiyithe qhiwu ngendebe endiyithiye ngegama elithi Umhlaba Umanzi. Umhlaba umanzi ziinyembezi zabalilayo, umanzi kukubila kwabasebenzi besombha eludakeni, ufumile ziinkathazo zeminyaka zesizukulwana sesizukulwana. Injongo endifuna ukuyifezekisa ngeli nqaku yeyokuba umntu achole ntwana ithile ngokujonga imeko esiphila kuzo gabalala, ekuhlaleni, emakhayeni ethu nakwii ndawo esixelenga kuzo. Mhlawumbi kuyakuvuseleleka iingcinga neenkumbulo zamhla-mnene, okanye ibophe nezilonda ezimanzi. Ukwanda kwaliwa ngumthakathi. . . Nangomso.,This thesis is presented in two parts: English and isiXhosa.
Keywords: Uncatalogued